2014
DOI: 10.1099/ijs.0.048264-0
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces catbensis sp. nov., isolated from soil

Abstract: Strain VN07A0015 T was isolated from soil collected on Cat Ba Island, Vietnam. The taxonomic position of strain VN07A0015 T was near Streptomyces aomiensis M24DS4 T (98.5 % 16S rRNA gene sequence similarity) and Streptomyces scabrisporus NBRC 100760 T (95.6 %), and it clustered within them; however, this cluster was distant from the type strains of other species of the genus Streptomyces. The aerial mycelia of strain VN07A0015 T were greyish and formed imperfect spiral spore chains (retinaculiaperti type) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A highly supported clade composed of S. aomiensis (Nagai et al, 2011 ), S. catbensis (Sakiyama et al, 2014 ), and S. seranimatus (Wang et al, 2007c ) was found to branch before S. scabrisporus but after S. thermoautotrophicus in the CCT. The three species share biochemical, cultural, and morphological features, notably the formation of smooth spores in straight to flexuous or looped spore chains, properties that distinguished them from their nearest phylogenetic neighbor, S. scabrisporus , which produces rugose ornamented spores in spiral chains (Ping et al, 2004 ; Wang et al, 2007c ; Sakiyama et al, 2014 ). In turn, S. seranimatus can be distinguished from all other Streptomycetaceae given the presence of PC in its polar lipid profile (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A highly supported clade composed of S. aomiensis (Nagai et al, 2011 ), S. catbensis (Sakiyama et al, 2014 ), and S. seranimatus (Wang et al, 2007c ) was found to branch before S. scabrisporus but after S. thermoautotrophicus in the CCT. The three species share biochemical, cultural, and morphological features, notably the formation of smooth spores in straight to flexuous or looped spore chains, properties that distinguished them from their nearest phylogenetic neighbor, S. scabrisporus , which produces rugose ornamented spores in spiral chains (Ping et al, 2004 ; Wang et al, 2007c ; Sakiyama et al, 2014 ). In turn, S. seranimatus can be distinguished from all other Streptomycetaceae given the presence of PC in its polar lipid profile (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…S1 (available in the online version of this article) whereas the major fatty acids were C 16 : 0 (22 %), iso -C 16 : 0 (18 %), anteiso -C 15 : 0 (14 %) and iso -C 15 : 1 (12 %). The presence of a high proportion of an unsaturated fatty acid is unusual in major members of the family Streptomycetaceae , but rather common in recently established genera such as Embleya and Yinghuangia [1, 4, 10, 11]. The in silico DNA G+C content of ‘ S. hyalinum ’ NBRC 13850 T was 71.7 %.…”
Section: Full-textmentioning
confidence: 99%
“…White to light grey aerial mycelium was observed on ISP 2-7 and glucose-asparagine agars. In contrast, substrate mycelium of E. scabrispora shows different colours such as pearl, and aerial mycelium was observed only on oatmeal agar (Table 2) [3,5,10]. Table 1 shows the morphological, cultural, cellchemical, physiological and biochemical characteristics of 'S.…”
mentioning
confidence: 99%
“…Isolate KRG-1 showed positive activity for nitrate reduction, alkaline phosphatase, β-galactosidase, α-glucosidase and gelatine hydrolysis. Majority of streptomycete species showed positive activity for the mentioned activities (Khan et al, 2010;Sakiyama et al, 2014).…”
Section: Taxonomic Identification Of the Most Active Strain Krg-1mentioning
confidence: 99%
“…To our knowledge, Streptomyces and Micromonospora species were reported capable of producing actinomycins (Kurosawa et al, 2006;Praveen, Tripathi, 2009). Antimycines were isolated for example from Streptomyces parvulus RSPSN2 (Keller et al, 2010), Streptomyces sindenensis (Praveen et al, 2008), Streptomyces avermitilis MS449 (Watkins et al, 1998), Streptomyces griseoruber (Shetty et al, 2014), Streptomyces nasri (Chen et al, 2012), Streptomyces chrysomallus (Sakiyama et al, 2014) and Streptomyces triostinicus (Praveen et al, 2009). There was a previous reports stating that also Streptomyces antibioticus produced actinomycin (El-Naggar, 1988; Singh et al, 2009) -however, not from South Africa and different species reported by different research groups may be the same species due to a lack of standard strain and not enough information regarding the characteristics of each strain (Shirling, Gottlieb, 1966).…”
Section: Antimicrobial Activity and Compound Identification Of The Momentioning
confidence: 99%